Efficient Sunlight-Induced Methylene Blue Removal over One-Dimensional Mesoporous Monoclinic BiVO4 Nanorods - Linrui Hou; Long Yang; Jiaoyang Li; Jie Tan; Changzhou Yuan (Journal of Analytical Methods in Chemistry)
Sunlight-driven mesoporous BiVO4 nanorods with monoclinic structure have been successfully synthesized via a simple hydrothermal method. The as-prepared one-dimensional BiVO4 nanorods exhibited high specific surface area due to their unique mesoporous structure. The mesoporous BiVO4 nanorods possessed strong photoabsorption properties in the visible light region as well as the ultravisible region, and the band gap was estimated to be ca. 2.18 eV. The photocatalytic activities were evaluated by decolorization of methylene blue under sunlight irradiation. Photocatalytic tests demonstrated that the decolorization rate of as-prepared mesoporous BiVO4 nanorods was even up to 98.8% in 180 min, much better than that prepared by solid-state reaction (23.1%) and the commercial TiO2 (Degussa P25) (14.2%) under the same conditions, due to their higher specific surface area and appropriate band gap. Moreover, the unique BiVO4 nanorods exhibit high stability after five photocatalytic degradation recycles.